Antidepressant Use in Pregnancy and the Risk of Cardiac Defects. Issue 2 (June 2015) - Huybrechts, K.F.; Palmsten, K.; Avorn, J.; Cohen, L.S.; Holmes, L.B.; Franklin, J.M.; Mogun, H.; Levin, R.; Kowal, M.; Setoguchi, S.; Hernández-Díaz, S.
<x xml:space="preserve">Abstract</x> (N Engl J Med. 2014;370(25):2397–2407)